Understanding the Behavior of Supercapacitor Materials via Electrochemical Impedance Spectroscopy: A Review - Perdana, Muhamad Yudatama; Johan, Bashir Ahmed; Abdallah, Muaz; Hossain, Md. Emdad; Aziz, Md. Abdul; Baroud, Turki Nabieh; Drmosh, Qasem Ahmed (Chemical record, 2024)
Energy harvesting and energy storage are two critical aspects of supporting the energy transition and sustainability. Many studies have been conducted to achieve excellent performance devices for these two purposes. As energy‐storing devices, supercapacitors (SCs) have tremendous potential to be applied in several sectors. Some electrochemical characterizations define the performance of SCs. Electrochemical impedance spectroscopy (EIS) is one of the most powerful analyses to determine the performance of SCs. Some parameters obtained from this analysis include bulk resistance, charge‐transfer resistance, total resistance, specific capacitance, response frequency, and response time. This work provides a holistic and comprehensive review of utilizing EIS for SC characterization. Overall, researchers can benefit from this review by gaining a comprehensive understanding of the utilization of electrochemical impedance spectroscopy (EIS) for characterizing supercapacitors (SCs), enabling them to enhance SC performance and contribute to the advancement of energy harvesting and storage technologies. Electrochemical Impedance Spectroscopy (EIS) is an advanced and facile technique for assessing supercapacitor performance. EIS data, particularly Nyquist plots, allow us to discern phenomena occurring in the electrode, electrolyte, or electrode‐electrolyte interface. This article presents a comprehensive review of studies on three types of supercapacitors: EDLC, pseudocapacitor, and hybrid supercapacitor, along with their corresponding EIS analyses.